2021
DOI: 10.1002/agj2.20525
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cover crop biomass nitrogen credits with Sentinel‐2 imagery and sites covariates

Abstract: Cover crops can positively impact productivity and the environment. While improved estimates of cover crop N benefits could help promote their adoption, little information is currently available at the broad scale. We conducted a multi-site study to determine whether use of satellite images and site factors could fill this gap. Six spectral indices were extracted from Sentinel-2 satellite imagery and used with modeling covariates to estimate cover crop properties and biomass N credits (biomass × N contents). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…However, if cover crops were managed properly, metaanalysis found that soil N 2 O emissions would be reduced or not affected compared to non-cover crop treatments considering the balance between increased SOC and reduced nitrate contents (Basche et al, 2014;Kaye and Quemada, 2017). The key to N 2 O mitigation in a diversified cropping system is, therefore, to avoid the overapplication of fertilizers by better estimating N balance that takes into account N credits from cover crops, which can be achieved through the use of remote sensing (Xia et al, 2020) and N calculators (Gaskin et al, 2019).…”
Section: Implications On Future Agricultural Management and Climate A...mentioning
confidence: 99%
“…However, if cover crops were managed properly, metaanalysis found that soil N 2 O emissions would be reduced or not affected compared to non-cover crop treatments considering the balance between increased SOC and reduced nitrate contents (Basche et al, 2014;Kaye and Quemada, 2017). The key to N 2 O mitigation in a diversified cropping system is, therefore, to avoid the overapplication of fertilizers by better estimating N balance that takes into account N credits from cover crops, which can be achieved through the use of remote sensing (Xia et al, 2020) and N calculators (Gaskin et al, 2019).…”
Section: Implications On Future Agricultural Management and Climate A...mentioning
confidence: 99%
“…This phenomenon, also known as equifinality, prevents the estimation of unique and recognizable parameter values (D. He et al., 2017). However, preparing crop growth and phenology for a large number of fields using standard ground‐based sample methods can be inconveniently time‐consuming, opening the way for the use of remote sensing datasets as a quick and low‐cost method (Ko et al., 2006; Maas, 1993; Xia et al., 2021). The integration of the developed APSIMr package with ANN acts as a scientific modeling workflow that provides fast, accurate, and low‐cost spatiotemporal simulation, which is very important for food security and nutritional analysis.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In the past two decades that the author has been involved in cover crop research, the tools available for this work have expanded to include new high‐tech tools such as unmanned arial vehicles (Roth & Streit, 2018; Yuan et al., 2019), remote sensing (Marcillo et al., 2020; Xia et al., 2021), hand‐held sensors (White et al., 2019), and mobile phone apps (Patrignani & Ochsner, 2015), but regardless of how high‐tech cover crop research becomes there will always be a need for accurate biomass sampling methods. Accurate sampling is critical to estimate field‐scale cover crop biomass production and associated metrics (nitrogen uptake, weed suppression, soil erosion control) and to “ground truth” and calibrate high‐tech tools that may provide new insights and more time efficient data collection.…”
Section: Discussionmentioning
confidence: 99%